Relationships between chemical structures and functions of triterpene glycosides isolated from sea cucumbers - Park, Joo-In; Bae, Hae-Rahn; Kim, Chang Gun; Stonik, Valentin A.; Kwak, Jong-Young (Frontiers in Chemistry, 2014)
Many marine triterpene glycosides have in vitro and in vivo activities with very low toxicity, suggesting that they are suitable agents for the prevention and treatment of different diseases, particularly cancer. However, the molecular mechanisms of action of natural marine compounds in cancer, immune and other various cells are not fully known. This review focuses on the structural characteristics of marine triterpene glycosides and how these affect their biological activities and molecular mechanisms. In particular, the membranotropic and membranolytic activities of frondoside A and cucumariosides from sea cucumbers and their ability to induce cytotoxicity and apoptosis have been discussed, with a focus on structure-activity relationships. In addition, the structural characteristics and antitumor effects of stichoposide C and stichoposide D have been reviewed along with underlying their molecular mechanisms.